Carbon nanodots as fluorescence probes for rapid, sensitive, and label-free detection of Hg2+ and biothiols in complex matrices - Zhou, Li; Lin, Youhui; Huang, Zhenzhen; Ren, Jinsong; Qu, Xiaogang (Chemical communications (Cambridge, England), 2012)
In this work, unmodified carbon nanodots are demonstrated as novel and environmentally-friendly fluorescence probes for the sensing of Hg(2+) and biothiols with high sensitivity and selectivity.In this work, unmodified carbon nanodots are demonstrated as novel and environmentally-friendly fluorescence probes for the sensing of Hg(2+) and biothiols with high sensitivity and selectivity.